The Urgency of Transpolitan Transmigration’s Regulation as an Effort to Accelerate National Development - Mailinda Eka Yuniza; Melodia Puji Inggarwati (Administrative and Environmental Law Review, 2021)
Nowadays the urgency of incorporating transpolitan transmigration, and a modern concept implements in transmigration, are important. Whereas the importants of transpolitan itself could accelerate the development in Indonesia. In order to to accelerate the national development, the urgency of transpolitan regulation is needed where the transpolitan play a huge role in it. The normative research type are used in this research. It showed that the government had directed every type of Transmigration in each stage to Transpolitan. Apart from that, Transpolitan transmigration also has its challenges given the inadequate legal structure in Indonesia, so it requires regulations on Transpolitan. It is argued that the application of Transpolitan can significantly accelerate development in Indonesia through the development of science and technology-based transmigration areas. Its explicitly discusses Transmigration in Indonesia and reflects the regulations in Indonesia. The findings provide information on a breakthrough in implementingTranspolitan, especially for stakeholders. In addition, this research can also be directed to enable the.